Greater Reduction in Abdominal Than in Upper Arms Subcutaneous Fat in 10- to 12-Year-Old Tennis Players: A Volumetric MRI Study - Sanchis-Moysi, Joaquín; Serrano-Sánchez, José Antonio; González-Henríquez, Juan José; Calbet, José A. L.; Dorado, Cecilia (Frontiers in Pediatrics, 2019)
Background. Little is known about the impact of long term participation in sports and subcutaneous fat volume in children. This study aimed at determining whether tennis participation is associated with lower subcutaneous adipose tissue volume (SATv) in the abdominal and upper extremities in children. Methods. Magnetic resonance imaging was used to determine the SATv stored in the abdominal region and upper arms in seven tennis players and seven inactive children matched by height and age (147 cm and 10.9 years). All participants were in Tanner stage 1 or 2. Results. Playing tennis was associated with 48% (P = 0.001) lower abdominal SATv and 17-18% (P > 0.05) lower upper arms SATv compared to controls. The ratio between abdominal/upper arms SATv was larger in the controls vs tennis players (69% P = 0.001). The SATv was similar in the dominant and non-dominant arm within each group. Conclusion. Playing tennis during childhood is associated with reduced SATv in the abdominal region and a more favourable regional distribution of fat. Despite the large amount of contractile activity of the playing (dominant) arm, there was no indication of between-arms differences in SATv.